The Effects of Reciprocal Teaching Learning Strategy and Self efficacy on Learning Outcomes of Early Childhood (AUD) Mathematical Logic - Erwanto, Erwanto; Maryatmi, Anastasia Sri; Budiyanto, Agung (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
The purpose of this research is to learn about the influence of Reciprocal Teaching and Self Efficacy on learning outcomes of AUD mathematical logic. This research is experimental research designed using treatment by level 2 × 2. The research method used is a variance analysis of two different cell paths. The results of this research are: (1) learning outcomes of students using Reciprocal Teaching strategy is higher than Ekspository strategy, (2) there is an interaction influence between learning strategy and self efficacy on learning outcomes of AUD mathematical logic, (3) there is an influence of self efficacy on learning outcomes of AUD mathematical logic.